Maqasid Sharia-Based Performance Improvement Model: A Case Study in Islamic Banks in Indonesia - Kartika, Indri; Kiryanto, Kiryanto; Cahyaningtyas, Rahayu Nur (UNISSULA, 2022)
This study aims to develop and analyze a maqosid sharia-based performance improvement model for Islamic banks in Indonesia. First, a comprehensive and relevant literature review is carried out to form a performance improvement model based on maqasid sharia. Furthermore, the model is tested empirically using statistical tests. The results show that Islamic social reporting (ISR) has a positive role in increasing maqasid sharia. Islamic corporate governance (ICG) likewise has a positive function in expanding Islamic social reporting. Islamic social reporting (ISR) does not mediate the relationship between Islamic corporate governance (ICG) and maqasid sharia. Islamic social reporting (ISR) does not mediate the relationship between Islamic corporate governance (ICG) and maqasid sharia. The implication of this result shows that Islamic commercial banks should give more consideration to the level of accomplishment of maqasid sharia, with the application of Islamic corporate governance (ICG) and the better implementation of Islamic social reporting (ISR) under the objectives of sharia banks. Regulators need to make policies in the form of incentives for Islamic banking to carry out their operations optimally and further realize maqasid sharia. The findings of this research have implications for policymakers, the need for a policy on the mandatory implementation of Islamic corporate governance (ICG). This study builds a model that can improve performance based on Islamic maqosid in Islamic banks in Indonesia.